Toward a Bidirectional and Co-Constructed Mentorship: Rethinking the Mentor and Student–Teacher Relationship. (November 2021) - Coppola, Rick; Rocha, Daniel J.; Woodard, Rebecca
Cooperating teachers are vital in the professional development of teacher candidates. Yet, little research has been done to explore the generative and bidirectional nature of mentoring in the context of a student teaching-mentoring dyad—including the ways that teacher candidates are vital to the professional development of cooperating teachers. This case study addresses this gap by exploring the realized potential of adopting a transformative activist stance in relation to the mentoring of a preservice teacher candidate. The strategic partnering of a veteran teacher (Rick) and undergraduate teacher candidate (Daniel)—both committed to culturally sustaining pedagogies—created an opportunity to reimagine the student teaching experience in one English language arts classroom. Through collaborative reflection and artifact analysis, we examine our roles in contributing to bidirectional mentorship that stressed innovative collaboration rather than adaptation to existing power differentials.